Medication review in German community pharmacies: post-hoc analysis of documented drug-related problems and subsequent interventions in the ATHINA-project - Seidling, Hanna; Send, Alexander Francesco Josef; Bittmann, Janina; Bruckner, Thomas; Haefeli, Walter E. (Research in social and administrative pharmacy, 2017)
Background: Any medication can cause drug-related problems (DRPs), which can often be detected by medication reviews. So far, only limited information is available on the practicability of systematic medication reviews in community pharmacies in daily routine and their value in Germany. Since 2012, the community pharmacy-centered medication review project “ATHINA - Arzneimitteltherapiesicherheit in Apotheken [medication safety in community pharmacies]” is endorsed by four Chambers of Pharmacists in Germany. The aim of this evaluation was to post-hoc analyze the nature of medication reviews performed in ATHINA. Methods: For this analysis, information from anonymized, structured documentation sheets of medication reviews performed from 2012 to 2015 were analyzed. Documentation sheets contained demographic information of the patient, the patient's medication, and structured information on any information need or DRP identified for a specific drug, the pharmacists' actions taken with regard to the identified problem (e.g. contact with a physician), and whether the problem was ultimately resolved completely, partly, or not at all. Results: Overall, 241 pharmacists documented 912 medication reviews with on average 10.8 ± 3.6 drugs. In 869 reviews (95.3%), the pharmacist documented at least one drug with information need or DRP. In 75.7% (N = 3972/5248) of the drugs with at least one information need or DRP, the pharmacists documented the action taken to solve the problem. At the end of the medication review, 359 (39.4%) of the cases had only drugs with resolved or no identified problems. Overall, the ratio of DRPs per drug regimen was reduced from 56% ± 22.7 drugs with at least one information need or DRP in the beginning to 28.9% ± 18.3 in the end. Conclusion: This analysis indicates that community pharmacists can deliberately identify patients with information needs and DRPs and solve many of these problems in the course of a medication review.